State Street, 1860-75 - Bradford, W. (Tufts Archival Research Center, 2005)
Elevated view looking east down State Street toward Broad Street. The view is of the buildings on the right side of the street taken from Exchange Street. The second building down on the right with the columns is the Exchange Building. The next street on the right is Kilby Street. Street lights are seen on both sides of the street. A few horse-drawn vehicles are also noticed. 9 3/8 x 9 15/16 overall 9 5/8 x 10 3/8 9 3/8 x 9 15/16 overall 9 5/8 x 10 3/8 Photomechanical prints